Social enterprises entrepreneur and social impacts to community: a review paper - Mohd Rizal Palil; Norul Syuhada Abu Hassan; Nur Aaina Aqilah Jamaluddin; Ida Suriya Ismail; Mas Ervina Samsuddin (Penerbit Universiti Kebangsaan Malaysia, 2023)
Numerous prior studies claimed that social enterprises had a beneficial effect (social impact) on addressing society's social problems. However, there is little evidence to support that statement. How well is this enterprise able to give an impact on solving social problems? Does it have any indicators that can prove the validity of its social impact? Therefore, this study aims to explore the literature review on social enterprise and their social impact, as well as to identify a few measurements to assess the social impact. Hence, the writing of this article was conducted based on reviewing the published literature including articles and journals which are relevant to the topic that can be accessed through online databases. Scopus, Science Direct and Google Scholar have been used for searching the articles needed. The search terms include "social enterprise" OR "social business" OR "social entrepreneurship” AND "Social impact" OR "measuring impact" OR "social impact measurement". This conceptual paper was motivated to get a deeper understanding of the social impact measurement employed by social enterprises. From the discussion, we have clearly defined the definition of social impact from different perspectives, including the importance of measuring the social impact among social enterprises has also been discussed briefly. Reviewed articles revealed that there is a wide range of methods for measuring social impact but in this article, we are focusing on three approaches only there are: balanced scorecard (BSC), social return on investment (SROI), and cost-benefit analysis (CBA) in this paper. This study summarises that measuring the social impact is becoming an essential determination for social enterprises as the key indicators of their performance to the communities or to the potential investors or funders. The study also suggests recommending further study of the social impact measurements that need to be discussed in depth and detail. This study's hope can attract more academicians to stimulate more research on this topic, specifically in measuring methods from Malaysia's perspective. The implication of this study forms a clear understanding of the social impact and a few of the measurements that can be used in measuring the impact of social enterprise.